Hubungan Antara Persepsi Pasien Tentang Kualitas dan Kemauan Membayar Pelayanan Kesehatan Gigi di MMC UMS - Karyadi, Edi; Murti, Bhisma (Jurnal Kesehatan, 2013)
Until now there is no standard for measuring the standard willingness to pay of patients andpatient satisfaction for the quality of dental care. Research purposes to assess the magnitude ofwillingness to pay for outpatient dental care and want to test the factors that affect willingness to pay foroutpatient dental care at the Muhammadiyah Medical Center (MMC UMS). This study was observationalanalytic study with cross-sectional approach, where all the variables studied were observed at the sametime. The study population was patients who received outpatient dental care with systematic sampling.To the adequacy of the sample required a minimum sample size of 120. The data collection by questionnairecontent validity technique. The results showed 60.8% of patient education level is college.Theaverage patient?s willingness to pay for dental care Rp.60.833. The average satisfaction score ofpatientson dental health services is 77.35 (including the high satisfaction category). While the averagepatientincome for Rp.2.110.417.Statisticalanalysis proves ?there is a positive correlation?betweenservicequality and willingness to pay for dental care patients (r = 0247, p <0.05). In this study alsoproves?there is a positive correlation? between the patient and the willingness to pay income dental care(r= 0.730, p <0.05). With the regression test showed the ?three variables (education, income andqualityof service)? jointly able to predict variations in the willingness of patients to pay for 59.7% andstatisticallyfit regression model (valid) (p <0.001).